The Effect of Visual, Spatial and Temporal Manipulations on Embodiment and Action - Ratcliffe, Natasha; Newport, Roger (Frontiers in Human Neuroscience, 2017)
The feeling of owning and controlling the body relies on the integration and interpretation of sensory input from multiple sources with respect to existing representations of the bodily self. Illusion paradigms involving multisensory manipulations have demonstrated that while the senses of ownership and agency are strongly related, these two components of bodily experience may be dissociable and differentially affected by alterations to sensory input. Importantly, however, much of the current literature has focused on the application of sensory manipulations to external objects or virtual representations of the self that are visually incongruent with the viewer’s own body and which are not part of the existing body representation. The current experiment used MIRAGE-mediated reality to investigate how manipulating the visual, spatial and temporal properties of the participant’s own hand (as opposed to a fake/virtual limb) affected embodiment and action. Participants viewed two representations of their right hand inside a MIRAGE multisensory illusions box with opposing visual (normal or grossly distorted), temporal (synchronous or asynchronous) and spatial (precise real location or false location) manipulations applied to each hand. Subjective experiences of ownership and agency towards each hand were measured alongside an objective measure of perceived hand location using a pointing task. The subjective sense of agency was always anchored to the synchronous hand, regardless of physical appearance and location. Subjective ownership also moved with the synchronous hand, except when both the location and appearance of the synchronous limb were incongruent with that of the real limb. Objective pointing measures displayed a similar pattern, however movement synchrony was not sufficient to drive a complete shift in perceived hand location, indicating a greater reliance on the spatial location of the real hand. The results suggest that while the congruence of self-generated movement is a sufficient driver for the sense of agency, the sense of ownership is additionally sensitive to cues about the visual appearance and spatial location of one’s own body.